Can you recommend me a good GP? Describing social differences in patient satisfaction within 31 countries. (21st December 2017) - Detollenaere, Jens; Hanssens, Lise; Schäfer, Willemijn; Willems, Sara
Abstract: Objective: This study aims to explore social differences in patient satisfaction of their general practitioner (GP) according to patient's gender, education, household income and ethnicity in Europe. Design: By using multilevel logistic modelling the impact of socioeconomic indicators (i.e. gender, education, household income and ethnicity) on patient satisfaction is estimated. In each model the authors controlled for indicators of person-focused care and strength of the primary care system. Setting: Primary care in 31 European countries. Participants: Patients who were sitting in the waiting room of the GP were asked to participate. They filled in the questionnaire after the consultation with the GP. Intervention: Describing social differences in patient satisfaction among European primary care patients. Main Outcome Measure(s): Patient satisfaction. Results: This study confirms previous research and reveals high levels of satisfaction with primary care in Europe. On average, 92.1% of the respondents would recommend their GP to their family or relatives. Variance in patient satisfaction is mostly explained at patient level, ~75% of the variance can be assigned to patient characteristics. Likewise, women, low-income groups and first generation migrants are less satisfied with their GP. Lastly, all indicators of person-focused care are positively associated with patient satisfaction, showing that the more person-focused the care, the higher the satisfaction among the patients. Conclusions: Notwithstanding the high satisfaction rates in Europe, patient satisfaction is still determined by patients' socioeconomic status (gender and household income), migration background and the degree of person-centred care. Therefore, policymakers and health professionals should target these population groups in order to improve the satisfaction rates in their country.